CARTIER INTERNATIONAL AG v BRITISH SKY BROADCASTING LTD. Issue 7 (28th August 2018) - ,
Abstract: H1 Trade marks – Website blocking injunctions – Counterfeit goods – Intermediaries – Internet service providers – "Mere conduits" – Jurisdiction – No specific implementation of art.11 of the Enforcement Directive in trade mark cases – Costs of implementation – Whether to be borne by intermediaries – Role of EU law – Whether costs of compliance the "quid pro quo" of immunities afforded to ISPs under EU law – Incidence of costs under English law – Extent of duties of ISPs to rights-holders – ISPs legally innocent in this case – Extent of any appropriate indemnity – Costs of the litigation – Discretion – Appeal to Supreme Court